The Sixteenth-Century Statutes of the Confraternity of San Francesco in Orvieto - Nerbano, Mara (Confraternitas, 2020)
This article presents the 1573 statutes of the flagellant confraternity of San Francesco in Orvieto (founded 1323) and provides a transcription of these statutes. It describes the manuscript, analyses its attribution to this confraternity, and briefly summarises the confraternity’s own history.